Sistem Informasi Magang Berbasis Web Framework Bootstrap 5 (Studi Kasus: Program Studi Informatika, Fakultas MIPA, Universitas Udayana) - Rahayuda, I Gede Surya; Watiniasih, Ni Luh; Santiari, Ni Putu Linda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
The purpose of this research is to overcome some of the problems in the apprenticeship process. From the identification results, the feasibility priority assessment using the APKL criteria identified a priority issue that must be resolved immediately, namely that the apprenticeship process has not been optimal. From the issues that have been analyzed using the APKL screening technique, an in-depth analysis is carried out using the fishbone technique. From several root causes, several creative ideas were obtained, and a main idea was concluded in the form of optimizing the apprenticeship process using a web-based information system. The main idea is embodied in five stages of research using the SDLC method. The system is designed using a DFD, and a relational scheme is used to design the database. The website was built using the Bootstrap 5 framework and added a mapping feature using leaflet.js. From the test results using the graph based black box testing method, good results are obtained, and all processes built can run as expected.     Keywords: APKL, fishbone, SDLC, bootstrap, leaflet.js, black box, graph based.